A simulated rover exploration of a long-lived hypersaline spring environment: The East German Creek (MB, Canada) Mars analogue site. (January 2021) - Cloutis, Ed; Applin, Daniel; Connell, Stephanie; Kubanek, Krista; Kuik, Jesse; Parkinson, Alexis; Ramirez, Mary; Turenne, Nathalie; Mertzman, Stanley
Abstract: We undertook a Mars rover-like deployment at a terrestrial analogue site consisting of active and relict perennial hypersaline springs at the East German Creek site in west-central Manitoba, Canada. This site serves as an analogue for possible long-lived springs on Mars. The deployment consisted of landing site-type investigations involving panoramic imagery from which regions of interest and targets of interest were selected for subsequent analysis by close-up imagery, and reflectance and Raman spectroscopy. These data were then used to prioritize samples for caching in the context of sample return. It was found that reflectance spectroscopy and Raman spectroscopy were complementary because they generally identified different minerals and phases. Reflectance spectra of the surfaces of whole rocks often differed from bulk powders of the same samples. Powdering of samples generally reduced the spectral contributions of the surface and grain coatings, allowing the identity of the "bulk rock" to be better determined. Raman spectra of powdered bulk samples were generally featureless due to induced fluorescence. Both spectroscopic techniques were equally effective at detecting biology at the site (cyanobacteria/chlorophyll). Biological activity could also be inferred from the crenulated texture of cyanobacterial mats. Post-deployment analysis of the samples was used to confirm and expand mineral identities, largely by X-ray diffraction (XRD) and elemental analysis. Mineral abundances, presence of phases undetectable by spectroscopy and XRD, and the pervasive presence of Fe oxyhydroxides could be addressed by X-ray fluorescence and wet chemistry. The deployment also provided valuable operational experience for current and next-generation planetary researchers. Overall, the results suggest that multiple analytical techniques, being the XRD, XRF, reflectance and Raman spectroscopy are highly complementary in exploring and characterizing a biology-hosting hypersaline springs environment. This work provides a framework for the value of different instruments for exploring similar sites on Mars, as the instrument from our field campaign have equivalents on the Perseverance and Rosalind Franklin rovers. Highlights: A high-fidelity rover campaign was conducted at a saline springs Mars analogue site. Imagery, reflectance, and Raman spectroscopy were applied to site characterization and sample triage. Imagery was useful for target-of-interest identification and prioritization. Reflectance and Raman spectroscopy were highly complementary for target-of-interest characterization.